THE COMPARISON OF TEACHING ENGLISH GRAMMAR BETWEEN FORMAL AND NON FORMAL EDUCATIONAL INSTITUTION A Case of Class A Semester II of Nursing Program in Stikes Jayapura in The Academic Year of 2010/2011 and The ABC English Course Sentani in The Academic Year - SUSIATI SUSIATI (DINAMIS, 2018)
This study is about teaching English grammar between formal and non formal educational institution, a case of class A nursing program in Stikes Jayapura in the academic year of 2010/2011 and the ABC English course Sentani in the academic year of 2011. This study focuses on the methods used by the English teachers at the both places and whether those applied methods affect the student’s achievement or not. This research methods in this study are grade observation, test, interview and questionnaire. Two kinds of obtained data in this study are qualitative and quantitative data. To analyze the qualitative data, the writer applies descriptive analysis. The writer describes the data obtained from the observation of the process of teaching and learning, interview and questionnaire in detail. Abstrak Penelitian ini tentang pembelajaran tata bahasa Inggris antara lembaga pendidikan formal dan non formal, yaitu pada program keperawatan kelas A di Stikes Jayapura pada tahun akademik 2010/2011 dan di tempat kursus bahasa Inggris ABC Sentani pada tahun akademik 2011. Penelitian ini berfokus pada metode yang digunakan oleh guru bahasa Inggris di kedua tempat tersebut dan apakah metode yang diterapkan mempengaruhi prestasi siswa atau tidak. Metode penelitian dalam penelitian ini adalah observasi kelas, tes, wawancara dan kuesioner. Dua jenis data yang diperoleh dalam penelitian ini adalah data kualitatif dan kuantitatif. Untuk menganalisis data kualitatif, penulis menggunakan analisis deskriptif. Penulis memaparkan data yang diperoleh dari pengamatan proses belajar mengajar, wawancara dan kuesioner secara detail. Kata Kunci : mengajar, grammar, pendidikan formal, pendidikan non formal